Relationship between Brand Personality and Management of Economics in Iraq - Atheer Abdulamer Al Mashady; Hana J Mohammed Al Askary; Huda Mahdi Hasan (International Journal of Supply Chain Management, 2019)
Through current research is intended disclosure to investigate the relationship and influence between the Brand Personality through the supply chain process. The research problem is identified in key question, Do brand personality play a role in arousing or creating a state of supply chain process with the customer, where consisted of two basic questions. But in order to confirm the hypothesis president underwent multiple tests to ensure their validity. The research use questionnaire to collect data. The data was analyzed using a variety of statistical methods and extracted results using statistical program SPSS v.20. The main conclusions of research is the responses of the research sample varied to the variable of brand sincerity by the sense of joy when dealing with that brand in addition to the benefit of its use. The key recommendations is marketing managers should take an interest in the idea of brand personality because it helps to differentiate the mark by developing the consumer's emotional aspects.